2011
DOI: 10.1111/j.1600-0625.2011.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid differentiation regulator 1 (Erdr1) is a proapototic factor in human keratinocytes

Abstract: Skin is constantly exposed to physical and chemical stressors. The exposure of keratinocytes to ultraviolet B (UVB) irradiation causes epidermal damage via induction of apoptosis. Erythroid differentiation regulator 1 (Erdr1) modulates growth and survival of cells under various stressful conditions, but the function of Erdr1 in human keratinocyte apoptosis has not been investigated so far. Here, we investigated the effect of Erdr1 on UVB-induced apoptosis in human keratinocytes and also examined the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…ERDR1 induces hemoglobin synthesis and is a stressrelated survival factor [17,18]. Recently, ERDR1 was reported to be a pro-apoptotic factor in human keratinocytes and an antimetastasis factor in mouse melanoma cells and human gastric cancer cells [19][20][21]. This study investigated whether ERDR1 has anti-cancer effects on immune cells, human primary NK cells, as well as cancer cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ERDR1 induces hemoglobin synthesis and is a stressrelated survival factor [17,18]. Recently, ERDR1 was reported to be a pro-apoptotic factor in human keratinocytes and an antimetastasis factor in mouse melanoma cells and human gastric cancer cells [19][20][21]. This study investigated whether ERDR1 has anti-cancer effects on immune cells, human primary NK cells, as well as cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, ERDR1 inhibits gastric cancer cell migration and invasion [21]. ERDR1 is expressed in human keratinocytes and is detected in the cultured supernatants of murine erythroleukemia cells [17,19]. Although ERDR1 is regarded as a metastasis suppressor in cancer cells, its role in immune cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erdr1 is a vesicleassociated secreted protein that is ubiquitously expressed (11,15). It has reported functions in keratinocytes and NK cells, although there are currently no known roles for Erdr1 in T lymphocytes (13,14). A knockout mouse model does not exist to study the role of Erdr1, and our attempts to make a whole-body knockout using Crisper/Cas9 technology revealed that loss of this gene is not tolerated in utero ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Erdr1 was originally identified in supernatants of B-cell leukemic cells and named for its hemoglobin-inducing activity on erythroid lines, but now has implicated roles in cellular survival, NK cytotoxicity, and metastasis; however, its function within T cells remains completely unexplored (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%